STUDENTS’ PERSPECTIVE ON EXAMPLES NON EXAMPLES TECHNIQUE APPLICATION IN TEACHING SPEAKING - Veni Nella Syahputri (Getsempena English Education Journal, 2018)
In mastering English, speaking skill is considered as the indicator of successful language learning therefore the students are expected to comprehend speaking skill as fluent as possible. In fact, most students face their high affective filter that drives them have low motivation, inhibition, and anxiety.For that reason, teacher plays an important role in delivering and applying the appropriate technique in teaching speaking. One of the recommended techniques that can be used by teachers is examples non examples technique. Examples non examples technique is an activity that encourages students to analyze and construct the meaning through the picture as an example. The objective of this study is to find out whether there is a positiveresponse from students in the implementation of examples non examples technique. The research methodology used in this study is qualitative research in which there were thirty students of Agriculture of Teuku Umar University in the second grade were considered as the respondents of this research. The data collected by distributing a set of questionnaire to the respondents and analyzed by using percentage formula based on Likert scale indicators: strongly agree, agree, disagree and strongly disagree. The result of the research showed that there are 77 % of the respondents have positive response toward the technique application. It means that the implementation of examples non examples technique became favorite technique to the students in mastering speaking since it can develop students’ critical thinking, can construct the concept through the pictures, increase students’ communicative competence, and has sense of togetherness while students work in group cooperatively.